Design of Intelligent Bicycle Status Indication Apparatus Based on STM32 Microcontroller - Weilun Tang (Indonesian Journal of Innovation and Applied Sciences (IJIAS), 2022)
As the improvement of people’s living standards, more and more motor vehicles are emerging on the roads, which pose a great threat to the bicycle riders on the same routes. Among all the road accidents, more than half are caused by the inadequacy of bicycle signals. To guarantee the safety of these bicycle riders, it is important to show the real-time status of bicycles. Basically, the research method of this paper is design, simulation, and virtual verification. Based on STM32 microcontroller, the overall design scheme of an intelligent bicycle status indication apparatus was proposed, and the hardware and software design was specified. After scheme design, simulation was carried out and showed that with high-performance STM32 microcontroller, the apparatus can promptly show the status of bicycles, and the alarm will ring when other vehicles are in the dangerous range. Theoretical analysis which includes graphical analysis and calculation was successfully conducted, which proved that this design can effectively serve as a status indication apparatus and protect the bicycle riders from collisions.